2011
DOI: 10.1007/s11033-011-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

Has-miR-146a polymorphism (rs2910164) and cancer risk: a meta-analysis of 19 case–control studies

Abstract: Epidemiological studies have evaluated the association between has-miR-146a polymorphism (rs2910164) and cancer risk. However, published data are still inconclusive. Here, we performed a meta-analysis to assess the relationship between has-miR-146a polymorphism (rs2910164) and cancer susceptibility until May 8, 2010. Nineteen published case-control studies including a total of 10,496 cases and 12,885 controls were acquired. Overall, Increased cancer risk was found in domain model (OR = 1.18, 95% CI: 1.03-1.35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 36 publications
6
37
0
Order By: Relevance
“…of human genome [10]. Recently, various studies focused on the pre-miRNA polymorphisms located on the stem-loop, such as pre-mir-196a2 rs11614913 [20], pre-mir-146a rs2910164 [21], pre-mir-499 rs3746444 [22,23]. In the present study, the G allele of pre-let7d rs10993081 was found to contribute an independent increased risk for MetS and this association may be partially due to its effect on glucose metabolism.…”
Section: Fig 3 Interaction Dendrogramsupporting
confidence: 53%
“…of human genome [10]. Recently, various studies focused on the pre-miRNA polymorphisms located on the stem-loop, such as pre-mir-196a2 rs11614913 [20], pre-mir-146a rs2910164 [21], pre-mir-499 rs3746444 [22,23]. In the present study, the G allele of pre-let7d rs10993081 was found to contribute an independent increased risk for MetS and this association may be partially due to its effect on glucose metabolism.…”
Section: Fig 3 Interaction Dendrogramsupporting
confidence: 53%
“…A previous experimental study indicated that MiRNA has a key influence on tumor biology and is related to the progression and prognosis of cancer, and that the high expression of miR-499A>G in serum was significantly associated with a longer survival of non-small cell lung cancer (Hu et al, 2010;Liu et al, 2011). Common single nucleotide polymorphisms in premiRNA, rs3746444 in miR-499A>G and rs2910164 in miR-146aG>C, have been studied in various cancers, such as breast cancer, gastric cancer, cervical squamous cell cancer and colorectal cancer (Catucci et al, 2010;Okubo et al, 2010;Gao et al, 2011;Zhou et al, 2011;Srivastava and Srivastava, 2012;Wang et al, 2012). However, the results of these studies were inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, association studies with small sample sizes lack statistical power and may produce conflicting conclusions. During the preparation of this manuscript, several metaanalyses concerning rs2910164 polymorphism and cancer risk were published (Gao et al, 2011;Qiu et al, 2011;Xu et al, 2011;Wang et al, 2012). However, these studies have not addressed the interaction of compounding factors.…”
Section: Introductionmentioning
confidence: 99%